Development of Kokami Learning Media to Improve Students' Ability to Think Creatively and Innovatively in PAI Learning Class VII SMP Negeri 6 Singosari, Malang Regency - Maulana, Muhammad Miftahul; Maimun, Agus; Nahrawi, Sudirman (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
This research addresses the limited development of interactive learning media aimed at enhancing students’creative and innovative thinking skills in Islamic Religious Education (PAI), despite its proven impact on motivation and learning outcomes. The study focuses on the development, validation, attractiveness, and effectiveness of Kokami learning media for Grade VII students at SMP Negeri 6 Singosari, Malang Regency. Utilizing a Research and Development (R&D) approach based on the Borg and Gall model as modified by Sugiyono, the research involved small (n=10) and medium (n=30) student groups. Data collection instruments included expert validation sheets, student response questionnaires, pretests, posttests, and interviews. Analysis employed descriptive statistics, the Likert and Guttman scales, and N-gain calculations. The development process followed nine steps, resulting in a validated media tool, with expert ratings exceeding 90% for both content and design. The media was rated highly attractive, receiving a 97.51% positive response from students. In terms of effectiveness, student learning outcomes improved from an average pretest score of 67.5 to a posttest score of 79.1, with an N-gain of 0.357, indicating moderate effectiveness. The study concludes that the Kokami media development process, particularly its six key stages plays a significant role in promoting creative and innovative thinking in PAI learning. The findings contribute theoretically to game-based learning media design and offer practical recommendations for educators to integrate interactive tools into religious education. Future research is encouraged to expand the sample size and further investigate the media’s impact on student interest and achievement across diverse contexts.